2014
DOI: 10.5625/lar.2014.30.2.84
|View full text |Cite
|
Sign up to set email alerts
|

An ethanolic extract ofAngelica gigasimproves atherosclerosis by inhibiting vascular smooth muscle cell proliferation

Abstract: The effects of an ethanolic extract of Angelica gigas (EAG) on the vascular smooth muscle cell (VSMC) proliferation and high-cholesterol diet-induced hypercholesterolemia and atherosclerosis were investigated. Rat aortic VSMCs were stimulated with platelet-derived growth factor-BB (25 ng/mL) for the induction of DNA synthesis and cell proliferation. EAG (1-10 µg/mL) significantly inhibited both the thymidine incorporation and cell proliferation in a concentration-dependent manner. Hypercholesterolemia was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…AG has been used in the treatment vascular disorders, however its molecular mechanism remains unclear (18)(19)(20)(21). The activation of RhoA may serve as an indicator for cold responses in vascular cells, however the cold-mediated mechanisms of RP remain to be elucidated (4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AG has been used in the treatment vascular disorders, however its molecular mechanism remains unclear (18)(19)(20)(21). The activation of RhoA may serve as an indicator for cold responses in vascular cells, however the cold-mediated mechanisms of RP remain to be elucidated (4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the biological and chemical efficacy of herbal medicines for the treatment of RP (4,(12)(13)(14)(15)(16). Angelica gigas (AG) is currently used for the management of vascular diseases, including menopausal symptoms (17,18), atherosclerosis (19) and brain ischemia (20). The anti-vasoconstrictive effect of AG has been demonstrated in vitro and in vivo (21,22), suggesting that AG may be useful in managing the vascular dysfunction observed in RP.…”
Section: Introductionmentioning
confidence: 99%
“…Acute dietary hypercholesterolemia was induced by feeding rabbits with a powdered HCD containing 0.5% cholesterol and 1% corn oil for 2 weeks, followed by 0.5% cholesterol for additional 10 weeks during treatment period [ 26 27 28 ]. After 2-week induction period, the animals were grouped (n=6/group) according to their blood cholesterol levels to adjust to similar mean values.…”
Section: Methodsmentioning
confidence: 99%
“…The sample was dissected in 5 cm long from the orifice of carotid artery, and opened longitudinally. After removing fats and tissues adhering to the adventitia, the aorta was dehydrated with 100% propylene glycol for 10 min, and stained with 0.7% Sudan IV (in propylene glycol) for 10 min [ 26 27 28 ]. Then, it was hydrated with 85% propylene glycol for 5 min, washed with distilled water, and photographed and analyzed with Digital Image Analyzer (Image Inside; Focus, Seoul, Korea) for red atheromatous plaques.…”
Section: Methodsmentioning
confidence: 99%
“…Jang et al also reported that the extract of A. gigas inhibited vascular smooth muscle cell proliferation due to the inhibitory potential on the DNA synthesis (Jang et al, 2014). In contrast, MyoD is a myogenic regulatory factor inducing the myogenic differentiation (Kim et al, 2017).…”
Section: Fatty Acid Metabolismmentioning
confidence: 99%